2024
DOI: 10.1002/biof.2050
|View full text |Cite
|
Sign up to set email alerts
|

The interlacing anticancer effect of pharmacologic ascorbate, chloroquine, and resveratrol

Kinga Makk‐Merczel,
Dóra Varga,
Péter Hajdinák
et al.

Abstract: Currently, a diagnosis with KRAS mutant pancreatic ductal adenocarcinoma (PDAC) means a death warrant, so finding efficient therapeutic options is a pressing issue. Here, we presented that pharmacologic ascorbate, chloroquine and resveratrol co‐treatment exerted a synergistic cytotoxic effect on PDAC cell lines. The observed synergistic cytotoxicity was a general feature in all investigated cancer cell lines independent of the KRAS mutational status and seems to be independent of the autophagy inhibitory effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The combination of RES with androgen receptor and CXCR4 antagonists has demonstrated efficacy in inhibiting PCa metastasis ( 69 ). It has been shown that RES can lead to cell cycle arrest: low concentrations of Res significantly decreased the ratio of G0/G1 populations, whereas high concentrations of Res increased this ratio ( 43 ).…”
Section: The Bioactivities Of Resmentioning
confidence: 99%
“…The combination of RES with androgen receptor and CXCR4 antagonists has demonstrated efficacy in inhibiting PCa metastasis ( 69 ). It has been shown that RES can lead to cell cycle arrest: low concentrations of Res significantly decreased the ratio of G0/G1 populations, whereas high concentrations of Res increased this ratio ( 43 ).…”
Section: The Bioactivities Of Resmentioning
confidence: 99%